1992
DOI: 10.1136/bmj.305.6853.554
|View full text |Cite
|
Sign up to set email alerts
|

Safety of early pain relief for acute abdominal pain.

Abstract: Objectives-(a) to determine the efficacy of papaveretum in treating pain when administered early to patients presenting with acute abdominal pain and (b) to assess its effect on subsequent diagnosis and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(62 citation statements)
references
References 5 publications
1
54
0
7
Order By: Relevance
“…Administration of opioids does not decrease the diagnostic accuracy of physical examination ((EL A2) [40,41,42,43,44,45,46]), nor does it influence choices made in treatment ((EL A2) [40,42]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of opioids does not decrease the diagnostic accuracy of physical examination ((EL A2) [40,41,42,43,44,45,46]), nor does it influence choices made in treatment ((EL A2) [40,42]).…”
Section: Resultsmentioning
confidence: 99%
“…Choice of antibiotics is dependent on local pathogens and national guidelines. Administration of opioids (analgesics) decreases the intensity of the pain and does not affect the accuracy of physical examination (level 1 [40,41,42,43,44]).…”
Section: Resultsmentioning
confidence: 99%
“…3,6,18,22 However, this study showed that the overall clinical impression was similar with or without pain control. The administration of analgesics did not appear to affect the patient's disposition.…”
Section: Discussionmentioning
confidence: 58%
“…49,79,82,83 There is no longer a rationale for withholding analgesics from cats because previously held misconceptions about complications associated with analgesics in the species have been largely discredited. 84,85 But we must remain vigilant for adverse effects in order to manage them correctly.…”
Section: Short Form Of the Glasgow Composite Pain Scalementioning
confidence: 99%